Metaphor of BPJS Kesehatan as a Sick Patient in Indonesian Media Headlines - Muhammad Adam (Hasanuddin University, 2020)
Indonesian health insurance (BPJS Kesehatan) has been facing financial deficit and during the coverage of its deficit, media frequently use many medical terms metaphor to describe the financial condition of BPJS Kesehatan. This study aims to examine the medical terms metaphor used to describe the financial deficit of BPJS Kesehatan to further identify the entailments and to pin point what is the cause of sickness and what could cure the sickness. Qualitative method is used in this study with conceptual metaphor theory (Lakoff and Johnson, 1980) as the conceptual framework. There 10 headlines from various online media outlet that are collected as the source of the data. The study examines the particular terms which described BPJS Kesehatan as a sick patient and further analysis is conducted to identify the closest entailments of metaphor, which are to identify who will be the doctor and what cause its sickness. The results shows that the particular conditions as metaphor used to describe the financial condition of BPJS Kesehatan is dying (sekarat), critical (kritis), swell (bengkak), and wound (luka). From the analysis of entailments, the doctor is the government equipped with medical supplies and procedures to cure the patient which is the financial subsidy and the second entailment is the cause of the sickness which is the lack of awareness from the member to pay the premium regularly on time.